Determination of Insect Fauna and Succession Important for Forensic Entomology in İstanbul Province - TURAN, YAVUZ (My University, 2024)
Although the use of insects in solving murders in Turkey is still in its infancy compared to other developed countries, it is seen that insects are used in solving some murders. İstanbul is the largest city in terms of population in Turkey. In parallel with this, İstanbul is one of the cities where the most murders are committed. For this reason, in this study, it was aimed to reveal the forensic entomologically important insect fauna and to determine the insect succession of İstanbul, where the most murder cases are seen. The study was carried out at Marmara University Başıbüyük Campus in Maltepe district on the Asian side of İstanbul, using four rabbit carcasses representing each season. At the end of the study, 33 species belonging to four insect orders were identified. Of these, 11 belonged to Diptera, 20 to Coleoptera, one to Hymenoptera and one to Hemiptera. In this study, insect succession was also examined and the succession of insect species coming to the carcass was revealed. This study is the first detailed study conducted in İstanbul province in terms of the detection of insect species which are important for forensic entomology.
Keywords: Yaşam Bilimleri; Hayvan Biyolojisi; Diğer; Temel Bilimler; Life Sciences; Animal Biology; Other; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Multidisipliner; Multidisciplinary